2016
DOI: 10.1016/j.marenvres.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The flip-or-flop boutique: Marine debris on the shores of St Brandon's rock, an isolated tropical atoll in the Indian Ocean

Abstract: Highlights• Marine debris was studied on 15 islets of St. Brandon's Rock, Indian Ocean • Plastics made up 79% of 50 000 debris items at 0.74 items m -1 shore length Intact CFLs suggests product-facilitated long-range transport of mercury. We suspect that aggregated marine debris, scavenged by the islands from currents and gyres, could re-concentrate pollutants. SBR islets accumulated debris types in different proportions suggesting that many factors act variably on different debris types. Regular cleaning of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Multiple studies sampled plastics on beaches in the Indian Ocean (Figure 1; Ryan, 1987;Slip and Burton, 1991;Madzena and Lasiak, 1997;Uneputty and Evans, 1997;Barnes, 2004;Jayasiri et al, 2013;Duhec et al, 2015;Nel and Froneman, 2015;Bouwman et al, 2016;Kumar et al, 2016;Imhof et al, 2017;Lavers et al, 2019), but because they used very different sampling methods on different timescales (Table A1), their results are difficult to compare. However, they do provide qualitative evidence that plastic is found on coastlines throughout the Indian Ocean, both on populated beaches close to plastic sources (Uneputty and Evans, 1997;Jayasiri et al, 2013;Kumar et al, 2016) as well as on remote, uninhabited coastlines and islands (Ryan, 1987;Slip and Burton, 1991;Madzena and Lasiak, 1997;Barnes, 2004;Duhec et al, 2015;Nel and Froneman, 2015;Bouwman et al, 2016;Imhof et al, 2017;Lavers et al, 2019). Which coastlines are most heavily affected by stranding plastics depends both on the location of plastic sources and the ocean dynamics in the region.…”
mentioning
confidence: 99%
“…Multiple studies sampled plastics on beaches in the Indian Ocean (Figure 1; Ryan, 1987;Slip and Burton, 1991;Madzena and Lasiak, 1997;Uneputty and Evans, 1997;Barnes, 2004;Jayasiri et al, 2013;Duhec et al, 2015;Nel and Froneman, 2015;Bouwman et al, 2016;Kumar et al, 2016;Imhof et al, 2017;Lavers et al, 2019), but because they used very different sampling methods on different timescales (Table A1), their results are difficult to compare. However, they do provide qualitative evidence that plastic is found on coastlines throughout the Indian Ocean, both on populated beaches close to plastic sources (Uneputty and Evans, 1997;Jayasiri et al, 2013;Kumar et al, 2016) as well as on remote, uninhabited coastlines and islands (Ryan, 1987;Slip and Burton, 1991;Madzena and Lasiak, 1997;Barnes, 2004;Duhec et al, 2015;Nel and Froneman, 2015;Bouwman et al, 2016;Imhof et al, 2017;Lavers et al, 2019). Which coastlines are most heavily affected by stranding plastics depends both on the location of plastic sources and the ocean dynamics in the region.…”
mentioning
confidence: 99%
“…Unlike the litter from the fishing industry, it is less likely that the main source of these is Seychelles: there are simply too many to imagine that they originate from a population of 98,000 people. The flip-flop phenomenon is not unique to Aldabra, and other studies throughout the region have reported large numbers and speculated about their origins 29,30,40 . Duhec et al 29 mention that flip-flops are the world's simplest, cheapest and most popular shoe 41 , especially in countries that fringe the Indian Ocean, where waste management is extremely poor.…”
Section: Discussionmentioning
confidence: 93%
“…Blickley et al, ). Often, the majority of the stranded litter consists of buoys, fishing nets and boxes (Blickley et al, ; Bouwman et al, ; Lavers & Bond, ; Pieper, Ventura, Martins, & Cunha, ; Ribic et al, ), very similar to the items found on RN and S&G Island. Microplastics are also accumulating on oceanic islands (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Despite their protection status, many oceanic MPAs are highly exposed to plastic pollution (Barnes et al, ; Lavers & Bond, ). AML has been identified as a serious threat in various oceanic MPAs, including the Pitcairn Islands MPA, the Pacific Remote Islands Marine National Monument, and others (Barnes et al, ; Blickley, Currie, & Kaufman, ; Bouwman, Evans, Cole, Choong Kwet Yive, & Kylin, ; Lavers & Bond, ; Ribic, Sheavly, & Klavitter, ). On all these islands, large amounts of AML have been found threatening the marine biodiversity.…”
Section: Discussionmentioning
confidence: 99%